Potassium isotopic composition of low-temperature altered oceanic crust and its impact on the global K cycle - Liu, Haiyang; Xue, Ying-Yu; Zhang, Guoliang; Sun, Wei-Dong; Tian, Zhen; Tuller-Ross, Brenna; Wang (王昆), Kun (Geochimica et cosmochimica acta, 2021)
To constrain the behavior of K isotopes during the low-temperature alteration of oceanic crust and reveal its impact on the global K cycle, we measured the K isotopic compositions of 49 fresh and altered basalts recovered from the Integrated Ocean Drilling Program (IODP) Sites U1365 (~100 Ma) and U1368 (~13.5 Ma) in the South Pacific Ocean. The measured basalts representing the uppermost oceanic crust have been subjected to low-temperature (<150 °C) alteration of different types and intensities as reflected by different secondary mineral modal abundances and element mobility. Both Sites have remarkably low sedimentation rates (0.71 and 1.1 m/Myr, respectively). The altered basalts from both Sites show higher K2O contents and K/Nb ratios than fresh basalts, suggesting the addition of K during low-temperature alteration. The measured δ41K values of the altered basalts vary over a large range (−0.76‰ to −0.17‰) compared to unaltered basalts, indicating significant K isotopic fractionation during low-temperature alteration of the oceanic crust. We propose that the K isotopic characteristics of the altered basalts were caused by the combined effects of equilibrium and kinetic isotopic fractionations between seawater and alteration minerals during the incorporation and adsorption of K into alteration minerals. A weighted average δ41K value of −0.40 ± 0.33‰ (2sd) is given for the low-temperature altered oceanic crust (AOC) at Sites U1365 and U1368, which is indistinguishable from the fresh N-MORB value (−0.44 ± 0.17‰), but significantly lower than its K source, i.e., seawater (δ41K = +0.12 ± 0.07‰, 2sd). Therefore, low-temperature AOC serves as an important sink for K and is a cause for the heavy K isotopic composition of seawater. In addition, the heterogeneous K isotopic compositions of the low-temperature AOC, together with large scale fractionation during various crustal processes, further highlights the utility of the K isotope system to trace subducted crustal materials.